PENINGKATAN KETERAMPILAN DAN HASIL BELAJAR PESERTA DIDIK KELAS XII MATERI INSEMINASI BUATAN PADA UNGGAS DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) DI SMK NEGERI 1 PANDAK - Yulia Suhartini (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
The aim of this research is to describe the process of implementing the learning model, student responses, skills and student learning outcomes after implementing the Project Based Learning (PJBL) learning model. This research is Classroom Action Research (PTK), which was conducted at SMK Negeri 1 Pandak in the 2023/2024 academic year, on learning outcomes for hatching eggs, the sub-material of artificial insemination in poultry. The research subjects were 32 students in class XII Poultry Agribusiness (ATU). Data collection methods use observation methods, questionnaires and practice assessment rubrics. The data analysis technique uses quantitative descriptive analysis. The research results prove that the Project Based Learning learning model has the ability to increase students' interest in learning which can influence learning outcomes, individually or in groups. Therefore, it can be concluded that the Project Based Learning learning model can be applied to the independent curriculum, in subjects, poultry breeding, production management elements in egg hatching learning outcomes, sub-material on artificial insemination in poultry.